Gap analysis of exceptional species—Using a global list of exceptional plants to expand strategic ex situ conservation action beyond conventional seed banking. (February 2022) - Pence, Valerie C.; Bruns, Emily Beckman; Meyer, Abby; Pritchard, Hugh W.; Westwood, Murphy; Linsky, Jean; Gratzfeld, Joachim; Helm-Wallace, Sara; Liu, Udayangani; Rivers, Malin; Beech, Emily
Abstract: With two in five plant species facing extinction, plant diversity loss demands action that integrates ex situ with in situ conservation approaches. While conservation in seed banks has been widely adopted, this technology cannot be applied to exceptional species, which require alternative approaches. We propose a new conceptual framework, resulting in the creation of a global working Exceptional Status List. Using a semi-automated method to evaluate over 23, 000 seed plants, 775 were identified as exceptional, <3% of those predicted to be exceptional. These were further characterized by one or more of four exceptionality factors (EF): Species with desiccation intolerant seeds (EF2, 50%), short-lived seeds (EF3, 36.6%), unavailable seeds (EF1, 12.6%), or deeply dormant seeds (EF4, 3.4%). One quarter of the identified exceptional species are threatened, and the four families with the most exceptional species were Dipterocarpaceae, Arecaceae, Rutaceae, and Fabaceae. Only 20% of plant genera have had even one species assessed for exceptionality. Although 688 exceptional species are in ex situ collections, most were represented by only 1–4 ex situ sites, primarily living plant collections, with very few in cryobanks. This project illustrates the significant gaps in our knowledge of exceptionality and the need for additional input from researchers and practitioners. The Exceptional Status List is provided as a conservation toolkit, to highlight gaps in knowledge and serve as the basis for further input and research, providing the basis for prioritizing goals and developing strategies for action to address the conservation challenges of exceptional plants. Highlights: We describe a global, working Exceptional Status List of over 23, 000 species. The basis for exceptionality is provided for 775 exceptional species. This work provides a basis for prioritizing species for conservation. The list will require additions and revisions from the scientific community. The list is provided for community use for developing conservation strategies.